2018
DOI: 10.1002/jcb.27551
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box protein A1 confers resistance to transforming growth factor‐β‐induced apoptosis in breast cancer cells through inhibition of Smad3 nuclear translocation

Abstract: Transforming growth factor-β (TGF-β) induces apoptosis of normal epithelial cells, such as mammary epithelium. Although breast cancer progression associates with acquisition of resistance to TGF-β-induced apoptosis, the molecular mechanisms underlying this resistance are largely unknown. Here, we show that forkhead box protein A1 (FOXA1), which is known as a pioneer transcription factor, suppresses TGF-β-induced apoptosis of estrogen receptor-positive breast cancer cells. FOXA1 is found to inhibit nuclear tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Some studies demonstrated that forkhead box protein A1 (FOXA1), a member of forkhead box gene superfamily, inhibits apoptosis in cancer cells [82,83]. Consistent with these in vitro data, Ren et al observed that gastric cancer patients with high expression of FOXA1 had poorer five-year overall survival [84].…”
Section: A Multitude Of Molecules Regulate Apoptosis and Hippo-yapmentioning
confidence: 89%
“…Some studies demonstrated that forkhead box protein A1 (FOXA1), a member of forkhead box gene superfamily, inhibits apoptosis in cancer cells [82,83]. Consistent with these in vitro data, Ren et al observed that gastric cancer patients with high expression of FOXA1 had poorer five-year overall survival [84].…”
Section: A Multitude Of Molecules Regulate Apoptosis and Hippo-yapmentioning
confidence: 89%
“…However, these approaches lack efficacy. In addition, the understanding of the molecular etiology of BC progression and development is poor [5]. Thus, it is crucial to explore innovative pathways and genes related to BC progression, along with the clinical outcome of patient therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Repeating the CUT&RUN experiments under optimized experimental conditions should help in investigating this hypothesis further. Alternatively, "DNA-free" FOXA1 might localize to the cytoplasm and inhibit nuclear translocation of other TFs to promote cell death [88].…”
Section: Discussionmentioning
confidence: 99%